Navigating Cultural Entropy: Leadership Strategies and Organizational Dynamics in Higher Education Institutions - Asni Mustika Rani; Syamsul Hadi Senen (West Science Journal Economic and Entrepreneurship, 2023)
This study aims to explore cultural entropy in higher education institutions, with a focus on understanding its impact on employee performance and organizational dynamics. The research investigates factors influencing cultural entropy, the relationship with leadership, and parallels with healthcare settings. Conducted as a systematic literature review, this research employs a bottom-up approach, reviewing articles from Scopus, Emerald, and Google Scholar (2010-2023). The analysis includes factors contributing to cultural entropy, leadership styles, and the impact on organizational performance in higher education. The findings reveal that cultural entropy in higher education is influenced by factors such as bureaucratic excess, unclear communication, and limited employee engagement. Transformational leadership emerges as a crucial factor in addressing cultural entropy, emphasizing the need for leaders who can instigate positive change and foster a culture of continuous learning. The research is limited by the relatively small body of literature on cultural entropy in higher education. Further research is needed to explore tailored approaches for diverse academic contexts and to develop specific interventions for mitigating cultural entropy in educational settings. The study underscores the importance of proactive leadership in managing cultural entropy. Higher education institutions can benefit from strategies inspired by successful interventions in healthcare settings. Implementing policies and supports to address employee stress and cultural entropy can contribute to a more balanced and sustainable work environment. This study contributes to the limited body of literature on cultural entropy within educational institutions, shedding light on its unique manifestations and challenges. The exploration of parallels between healthcare and academia provides a novel perspective, emphasizing the distinct dynamics at play in educational settings. The study encourages further investigation into tailored approaches for addressing cultural entropy in diverse academic contexts.